FAKTOR PENENTU WISATAWAN MELAKUKAN STAYCATION DI BADUNG, BALI PADA MASA PANDEMI COVID-19 - Priscilla Nivili; I Made Kusuma Negara; Yayu Indrawati (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2022)
This study aims to determine the motivational factor that determines the domestic tourist to do the staycation activities in Badung Regency during the Covid-19. Data collection technique in this study using the questionnaire, the interview, observation, and literature review. The types and sources of data in this study used quantitative and qualitative data as well as primary and secondary data. Sampling itself using purposive sampling technique with data analysis using factor analysis with the help of SPSs. The results of this study found that there were six new factors that determine the motivational factor of the tourist doing the staycation activities in Badung Regency during the COVID19. These factors were, activity, health protocol, perception, purpose, marketing, and personal. The activities factor include visiting relatives, tourist attractions, and culture. The health protocol includes pandemic protocol, availability of the CHSE certificates, and the certainty there is no crowd. The perception factors include prestige, wish fulfillment, advertising, incentive Scheme. The purpose factor includes escape, relaxation, and play. The marketing factor includes social interaction, special events, and marketing. The personal factor includes romance, and location. While one indicator which is selffulfillment. This study did not involve any of the new factors due to its loading factor not passing the minimum value to the new factor. Self-fulfillment is an obligation to find what is the meaning inside a person after doing new things.